2015
DOI: 10.1007/s12639-015-0664-2
|View full text |Cite
|
Sign up to set email alerts
|

Anticestodal properties of Hibiscus rosa-sinensis L. (Malvaceae): an in vitro and in vivo study against Hymenolepis diminuta (Rudolphi, 1819), a zoonotic tapeworm

Abstract: The aim of this study was to investigate the in vitro and in vivo anticestodal effects of methanol extract of Hibiscus rosa-sinensis L. (Malvaceae) leaf against Hymenolepis diminuta (Rudolphi, 1819), a zoonotic tapeworm. Under the in vitro study, H. diminuta worms were exposed to 10, 20 and 40 mg/ml concentrations of methanol leaf extract and the effects were judged on the basis of physical motility/mortality of worms. On the other hand, in the case of in vivo study, H. diminuta infected rats were treated indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Regarding the anthelmintic studies on medicinal plants it emerges that various previous workers have assessed the anthelmintic potentials of different medicinal plants using either in vitro assays (Vijaya and Yadav 2014) or in vivo models (Tangpu et al 2004;Yadav and Temjenmongla 2012). However, it is only in few cases that an attempt has been made to employ both in vitro and in vivo tests to comment upon precisely the anthelmintic effects of a particular medicinal plant (Nath and Yadav 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the anthelmintic studies on medicinal plants it emerges that various previous workers have assessed the anthelmintic potentials of different medicinal plants using either in vitro assays (Vijaya and Yadav 2014) or in vivo models (Tangpu et al 2004;Yadav and Temjenmongla 2012). However, it is only in few cases that an attempt has been made to employ both in vitro and in vivo tests to comment upon precisely the anthelmintic effects of a particular medicinal plant (Nath and Yadav 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Acorus calamus Linn. and Hibiscus rosa-sinensis L., showed significant anthelmintic activity against the cestode parasite, Hymenolepis diminuta [9,10]. Cynodon dactylon L. Pers and Elaeocarpus floribundus also showed anthelmintic efficacy against Hymenolepis diminuta, both in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo assay revealed that at the highest dose, rats infected with H. diminuta, showed a higher reduction of worm and EPG counts as compared to mice infected with S. obvelata. In a similar study by Nath and Yadav (2015), the leaf extract of Hibiscus rosa-sinensis showed promising anticestodal efficacy. Interestingly in a similar study by Gogoi and Yadav (2016), the methanolic extract of Caesalpinia bonducella showed a better in vivo nematicidal efficacy.…”
Section: Discussionmentioning
confidence: 85%